Offshore Landward Motion Shortly After a Subduction Earthquake Implies Rapid Relocking of the Shallow Megathrust. Issue 1 (6th January 2023) - D'Acquisto, Mario; Govers, Rob
Abstract: Geodetic observations after large subduction earthquakes reflect multiple postseismic processes, including megathrust relocking. The timing of relocking and the observational constraints on it are unclear. Relocking was inferred to explain some observed landward motion that occurs within months. It was also considered unable to explain other, greater landward motion, including that off the coast of Japan beginning weeks after the 2011 Tohoku earthquake, attributed to postseismic relaxation. We use generic, 3D numerical models to show that relocking, particularly of the shallow interface, is needed for postseismic relaxation to produce landward motion on the tip of the overriding plate. We argue that this finding is consistent with previous simulations that implicitly relock the megathrust where afterslip is not included. We conclude that the Tohoku megathrust relocked within less than 2 months of the earthquake. This suggests that the shallow megathrust probably behaves as a true, unstably sliding asperity. Plain Language Summary: In the largest earthquakes, a tectonic plate suddenly slides under another, where previously the interface between them was largely locked. The deformation of the Earth's surface reflects multiple deep processes. One process is the restoration of interface locking. This means that elastic energy starts to accumulate again, building up toward the next earthquake. How long after an earthquake does the interface relock? Relocking is suggested to have caused some deformation observed months after some earthquakes, and so to have occurred by then. It is also thought to not explain the rapid landward motion of the seafloor on the upper plate, observed beginning less than 2 months after the 2011 Japan earthquake. We use numerical simulations to show that locking the shallow portion of the plate interface is needed for landward motion to transmit from the lower plate to the upper plate, as happened in Japan. Landward motion is understood to occur below and in the lower plate because of mantle flow and deep sliding taking place after the earthquake and caused by it. We conclude that this result agrees with simulations in previous studies, even though they were not interpreted in terms of locking by their authors. Key Points: Landward motion of the overriding plate, attributed to postseismic relaxation, was observed offshore 2 months after the Tohoku earthquake Models show that landward motion only transmits from the slab to the overriding plate, reaching the surface, if the megathrust is locked Observations imply shallow megathrust relocking within 2 months of the Tohoku earthquake, consistent with unstably sliding behavior